PENGARUH GAYA HIDUP DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pelanggan X2 Family Resto and Karaoke Kupang) - Susanti Oktafiani Tana; Juita L D Bessie (Universitas Nusa Cendana, 2020)
This study aims to a) Knowing and analyze customer perceptions of lifestyle, service quality andpurchasing decisions at X2 Family Resto and Karaoke Kupang. b) Knowing and analyze theinfluence of lifestyle and service quality partially on customers purchasing decisions at X2 FamilyResto and Karaoke Kupang. c) Knowing and analyze the influence of lifestyle and service qualitysimultaneously on customer purchasing decisions at X2 Family Resto and Karaoke Kupang. Thepopulation in this study are all customers who have visited and used services of the X2 FamilyResto and Karaoke Kupang. Samples taken as many as 100 respondents using accidental samplingtechnique. The analysis tecnique used is Quantitative Descriptive Analysis and multiple regression(R2). Based on the results of descriptive analysis shows customer perceptions of lifestyle and servicequality included in the satisfied category. In this study the regression equation was obtained: Y =1,620 + 0,264 X1 + 0,725 X2. If seen from the score scale, then the lifestyle variable equal is 4,27and the highest of the service quality variable is 4,29. Based on the analysis of statistical data, theresults of the t test show that the two independent variables have a significant effect on the variable.F test results show that simultaneosly the independent variable significantly influences theindependent variable. The R square adjust value of 0.782 shows that 78.2% of the purchase decisionvariable is influenced by the independent variable in the regression equation while the remaining21.8% is influenced by the variables not discussed in this study. It is recommended for X2 FamilyResto and Karaoke Kupang to add market segments and product development, which is not only foradolescents (Students) but also added to the adult market segmen and further researchers areexpected to add other aspects such as place, promotion, atmosfer, service, brand awareness,andbrand image. Keywords: Lifestyle, Service Quality and Purchasing decisions